Simultaneous Travel and Hoist Maneuver Input Shaping Control Using Frequency Modulation - Sameer Arabasi; Ziyad Masoud (Shock and Vibration)
This paper presents an input shaping control system for overhead crane operations involving simultaneous hoist and travel maneuvers. The control system utilizes model-based partial feedback linearization with frequency modulation. Traditional input shaping controllers target specific system frequencies. Therefore, they are incapable of accommodating the time dependant frequency associated with simultaneous hoist and travel crane maneuvers. Frequency modulation is used to tune the time-dependent system frequency to the design frequency of a primary input shaping controller. Partial feedback linearization is used to eliminate the time-dependent damping of the system. The primary input shaper frequency is based on lowest operating frequency of the system associated with the longest hoisting cable length operation. Simulations results, using primary zero-vibration (ZV) and zero-vibration-derivative (ZVD) input shapers, are presented. General arbitrary input travel and hoist commands are simulated. Results demonstrate the ability of the proposed control system to eliminate residual oscillations in all simulated cases.